Çalışma yaşamında kadın yöneticiler ve İstanbul Belediyeleri örneği - Yalman, Dilan (My University, 2020)
Hem dünyada hem Türkiye’de kadınların çalışma yaşamına katılım oranı artmasına rağmen yönetim kademelerinde yeterince yer bulamamaktadırlar. Kadınlar bulundukları sektörde kariyer basamaklarını tırmanırken birden fazla engelle karşılaşmaktadır. Toplumun erkeğe ve kadına biçtiği rollerden kaynaklı olarak güçlü liderlik gerektiren konumlara kadınların gelmesi zorlaşmaktadır.Yapılan araştırmada kadınların çalışma yaşamında ve yönetici konumunda yaşadıkları zorluklar incelenmiştir. Araştırmada İstanbul belediyelerinde görev alan genel sekreter, daire başkanı, genel müdür, başkan yardımcısı, müdür olmak üzere toplam 17 kişiyle derinlemesine görüşme yapılmıştır. Kadın yöneticiler ile yapılan görüşme sonucunda üst makam tarafından iş yapma kapasitesi, insan ilişkileri iyi olan, kolay iletişim kurabilen, yönetimle aynı dili konuşan ve uyumlu, yöneticilik vasfına sahip olan kişilerin yönetici olarak seçildiği tespit edilmiştir. Ayrıca kadın yöneticiler, kadınların, çalışma hayatının bir parçası olduklarının farkına varması, eğitime önem vermesi, cesur, özgüveni yüksek, planlı, disiplinli olması ve beşeri ilişkilerinin iyi olması gibi niteliklere vurgu yapmışlardır.

Despite both in Turkey and in the world to increase the ratio of women's participation in working life can not find enough in management positions. Women encounter more than one obstacle while climbing the career ladder in their sector. Due to the roles assigned by the society to men and women, it is difficult for women to reach positions that require strong leadership.In the study, the difficulties women experience in working life and in managerial positions were examined. The research was applied to a total of 17 people, including the general secretary, head of department, general manager, vice president and director, working in Istanbul municipalities. In the field research, the interview technique was applied by using a recording device as a means of gathering information, deciphered and transferred to the computer environment. As a result of the interviews with the female managers, it was determined that the people who have good business capacity, good human relations, easy communication, speak the same language with the management and are compatible, and have managerial qualifications were selected as managers. In addition, when the suggestions of female managers regarding the working life of women were asked, they gave information about the necessity of realizing that they are a part of working life, giving importance to education, being courageous, self-confident, planned, disciplined, being good in human relations.
Keywords: Belediye; Carrer Barriers; Kadın İstihdamı; Kadın Yönetici; Kadın yöneticiler; Kariyer Engelleri Women Employment; Local government; Municipalities; Women executives; Women Manager; Yerel yönetim